If you find any mistakes, please make a comment! Thank you.

Solution to Principles of Mathematical Analysis Chapter 8 Part B


Chapter 8 Some Special Functions

Exercise 13

(By analambanomenos) The Fourier coefficients for $f$ are (letting $n\ne 0$ and using $e^{i2\pi n}=1$)
\begin{align*}
c_0 &= \frac{1}{2\pi}\int_0^{2\pi}x\,dx \\
&= \frac{1}{2\pi}\bigg(\frac{(2\pi)^2-0}{2}\bigg) \\
&= \pi \\
c_n &= \frac{1}{2\pi}\int_0^{2\pi}xe^{-inx}\,dx \\
&= \frac{1}{2\pi}\bigg(\frac{2\pi}{-in}-0\bigg)-\frac{1}{2\pi}\cdot\frac{1}{-in}\int_0^{2\pi}e^{-inx}\,dx \\
&= -\frac{1}{in}+\frac{1}{2\pi in}\cdot\frac{1-1}{-in} \\
&= \frac{i}{n}.
\end{align*}Hence by Parseval’s theorem
\begin{align*}
\sum_{-\infty}^\infty|c_n|^2 &= \frac{1}{2\pi}\int_0^{2\pi}x^2\,dx \\
\pi^2 + 2\sum_1^\infty\frac{1}{n^2} &= \frac{4\pi^2}{3} \\
\sum_1^\infty\frac{1}{n^2} &= \frac{1}{2}\bigg(\frac{4\pi^2}{3}-\pi^2\bigg) = \frac{\pi^2}{6}
\end{align*}


Exercise 14

(By analambanomenos) The maximum local rate of change of $f$ will occur at the multiples of $2\pi$, where $\lim|f’|=2\pi$. Hence $f$ satisfies the condition of Theorem 8.14 with constant $M=2\pi$, so we can conclude that the Fourier series of $f$ converges to $f(x)$ for all $x$.

Here are the Fourier coefficients of $f$ (where $n\ne 0$, and using $e^{in\pi}=e^{-in\pi}$ for all integers $n$):
\begin{align*}
c_0 &= \frac{1}{2\pi}\int_{-\pi}^0(\pi+x)^2\,dx+\frac{1}{2\pi}\int_0^\pi(\pi-x)^2\,dx \\
&= \frac{1}{2\pi}\bigg(\frac{\pi^3}{3}+\frac{\pi^3}{3}\bigg) \\
&= \frac{\pi^2}{3} \\
c_n &= \frac{1}{2\pi}\int_{-\pi}^0(\pi^2+2\pi x+x^2)e^{-inx}\,dx+\frac{1}{2\pi}\int_0^\pi(\pi^2-2\pi x+x^2)e^{-inx}\,dx \\
&= \frac{1}{2\pi}\int_{-\pi}^\pi(\pi^2+x^2)e^{-inx}\,dx+\int_{-\pi}^0xe^{-inx}\,dx-\int_0^\pi xe^{-inx}\,dx \\
\end{align*} \begin{align*}
\frac{1}{2\pi}\int_{-\pi}^\pi(\pi^2+x^2)e^{-inx}\,dx &= \frac{1}{2\pi}\cdot\frac{i}{n}(2\pi^2e^{-in\pi}-2\pi^2e^{in\pi})-\frac{1}{2\pi}\cdot\frac{2i}{n}\int_{-\pi}^\pi xe^{-inx}\,dx \\
&= 0-\frac{i}{\pi n}\cdot\frac{i}{n}(\pi e^{-in\pi}+\pi e^{in\pi})+\frac{i}{\pi n}\cdot\frac{i}{n}\int_{-\pi}^\pi e^{-inx}\,dx \\
&= \frac{1}{n^2}(e^{-in\pi}+e^{in\pi})-\frac{i}{\pi n^2}(e^{-in\pi}-e^{in\pi}) \\
&= \frac{1}{n^2}(e^{-in\pi}+e^{in\pi}) \\
\end{align*} \begin{align*}
\int_{-\pi}^0 xe^{-inx}\,dx &= \frac{i}{n}(0e^0+\pi e^{in\pi})-\frac{i}{n}\int_{-\pi}^0 e^{-inx}\,dx \\
&= \frac{i\pi}{n}e^{in\pi}-\frac{i}{n}\cdot\frac{i}{n}(e^0-e^{in\pi}) \\
&= \frac{i\pi}{n}e^{in\pi}+\frac{1}{n^2}(1-e^{in\pi}) \\
\end{align*} \begin{align*}
\int_0^\pi xe^{-inx}\,dx &= \frac{i}{n}(\pi e^{-in\pi}-0e^0)-\frac{i}{n}\int_0^\pi e^{-inx}\,dx \\
&= \frac{i\pi}{n}e^{-in\pi}-\frac{i}{n}\cdot\frac{i}{n}(e^{-in\pi}-e^0) \\
&= \frac{i\pi}{n}e^{-in\pi}+\frac{1}{n^2}(e^{-in\pi}-1) \\
\end{align*} $$c_n=\frac{1}{n^2}(e^{-in\pi}+e^{in\pi})+\frac{i\pi}{n}e^{in\pi}+\frac{1}{n^2}(1-e^{in\pi})-\frac{i\pi}{n}e^{-in\pi}-\frac{1}{n^2}(e^{-in\pi}-1)=\frac{2}{n^2}$$ Hence
\begin{align*}
f(x) &= \frac{\pi^2}{3}+\sum_{|n|\ne 0}\frac{2}{n^2}e^{inx} \\
&= \frac{\pi^2}{3}+\sum_{n=1}^\infty\frac{2}{n^2}(e^{inx}+e^{-inx}) \\
&= \frac{\pi^2}{3}+\sum_{n=1}^\infty\frac{4}{n^2}\cos nx
\end{align*}Letting $n=0$, we get
\begin{align*}
\frac{\pi^2}{3}+4\sum_{n=1}^\infty\frac{1}{n^2} &= \pi^2 \\
\sum_{n=1}^\infty\frac{1}{n^2} &= \frac{\pi^2}{6}
\end{align*}And by Parseval’s theorem, we get
\begin{align*}
\frac{\pi^4}{9}+2\sum_{n=1}^\infty\frac{4}{n^4} &= \frac{1}{2\pi}\int_{-\pi}^0(\pi+x)^4\,dx+\frac{1}{2\pi}\int_0^\pi(\pi-x)^4\,dx \\
\frac{\pi^4}{9}+8\sum_{n=1}^\infty\frac{1}{n^4} &= \frac{1}{2\pi}\cdot\frac{1}{5}(\pi^5+\pi^5) \\
\sum_{n=1}^\infty\frac{1}{n^4} &= \frac{1}{8}\bigg(\frac{\pi^4}{5}-\frac{\pi^4}{9}\bigg) \\
\sum_{n=1}^\infty\frac{1}{n^4} &= \frac{\pi^4}{90}
\end{align*}


Exercise 15

(By analambanomenos) We want to show that $$\sum_{n=0}^ND_n(x)=\frac{1-\cos(N+1)x}{1-\cos x}.$$ I’ll show this by induction. It is true for the case $N=0$ since both sides equal 1, so assume that
$$\sum_{n=0}^{N-1}D_n(x)=\frac{1-\cos Nx}{1-\cos x}.$$ Then we have
\begin{align*}
(1-\cos x)\sum_{n=0}^ND_n(x) &= (1-\cos x)\sum_{n=0}^{N-1}D_n(x) + (1-\cos x)D_N(x) \\
&= (1-\cos Nx)+\frac{(1-\cos x)\sin(N+1/2)x}{\sin(x/2)} \\
&= (1-\cos Nx)+\frac{2\sin^2(x/2)\sin(N+1/2)x}{\sin(x/2)} \\
&= (1-\cos Nx)+2\sin(x/2)\sin(N+1/2)x \\
&= (1-\cos Nx)+\big(\cos Nx-\cos(N+1)x\big) \\
&= 1-\cos(N+1)x
\end{align*}Dividing both sides by $(1-\cos x)$ gives the desired result.

(a) Since $\cos x\le 1$ for all $x$, we have $1-\cos(N+1)x\ge 0$ and $1-\cos x\ge 0$, hence $K_N(x)\ge 0$.

(b) For $n\ne 0$, $$\int_{-\pi}^\pi e^{inx}\,dx=\frac{1}{in}(e^{in\pi}-e^{-in\pi})=0$$ since $e^{in\pi}=e^{-in\pi}$ for all all integers $n$. Hence $$\frac{1}{2\pi}\int_{-\pi}^\pi
D_N(x)\,dx=\frac{1}{2\pi}\int_{-\pi}^\pi e^0\,dx=1,$$ and so $$\frac{1}{2\pi}\int_{-\pi}^\pi K_N(x)\,dx=\frac{1}{N+1}\sum_{n=0}^N\frac{1}{2\pi}\int_{-\pi}^\pi D_n(x)\,dx=\frac{1}{N+1}(N+1)=1.$$

(c) Since $1-\cos x$ monotonically decreases from 2 to 0 on $[-\pi,0]$ and monotonically increases from 0 to 2 on $[0,\pi]$, we have $1-\cos x\ge1-\cos\delta$ on $[-\pi,-\delta]\cup[\delta,\pi]$. Also, the maximum value of $1-\cos(N+1)x$ is 2, so $$K_N(x)=\frac{1}{N+1}\cdot\frac{1-\cos(N+1)x}{1-\cos x}\le\frac{1}{N+1}\cdot\frac{2}{1-\cos\delta}$$ for $0<\delta\le|x|\le\pi$.

By (78) in the text, we have
\begin{align*}
\sigma_N(f;x) &= \frac{1}{N+1}\sum_{n=0}^Ns_n(f;x) \\
&= \frac{1}{N+1}\sum_{n=0}^N\frac{1}{2\pi}\int_{-\pi}^\pi f(x-t)D_N(t)\,dt \\
&= \frac{1}{2\pi}\int_{-\pi}^\pi f(x-t)\Bigg(\frac{1}{N+1}\sum_{n=0}^N D_N(t)\Bigg)\,dt \\
&= \frac{1}{2\pi}\int_{-\pi}^\pi f(x-t)K_N(t)\,dt
\end{align*}Let $\varepsilon>0$. Since $f(x)$ is uniformly continuous on $[-\pi,\pi]$, there is a $\delta>0$ such that $\big|f(x-t)-f(t)\big|<\varepsilon/2$ if $|t|\le\delta$. Also, $f(x)$ has a maximum value $M$ on $[-\pi,\pi]$. Using (a), (b), and (c), we have
\begin{align*}
\big|f(x)-\sigma_N(f;x)\big| &= \Bigg|\frac{1}{2\pi}\int_{-\pi}^\pi\big(f(x)-f(x-t)\big)K_N(t)\,dt\Bigg| \\
&\le \frac{1}{2\pi}\int_{-\pi}^\pi\big|f(x)-f(x-t)\big|K_N(t)\,dt \\
&\le \frac{1}{2\pi}\int_{-\pi}^{-\delta}2M\cdot\frac{1}{N+1}\cdot\frac{2}{1-\cos\delta}\,dx + \frac{1}{2\pi}\int_{-\delta}^\delta\frac{\varepsilon}{2} K_N(t)\,dt \;+ \\
&\phantom{\le}\;\;\frac{1}{2\pi}\int_\delta^\pi 2M\cdot\frac{1}{N+1}\cdot\frac{2}{1-\cos\delta}\,dx \\
&\le \frac{4M}{N+1}\cdot\frac{1}{1-\cos\delta}+\frac{\varepsilon}{2} \\
&\le \varepsilon
\end{align*}for large enough $N$. That is, $\sigma_N(f;x)\rightarrow f(x)$ uniformly on $[-\pi,\pi]$.


Exercise 16

(By analambanomenos) Let $\varepsilon>0$ and let $\delta>0$ such that $\big|f(x-t)-f(x+)\big|<\varepsilon/2$ for $-\delta<t<0$ and $\big|f(x-t)-f(x-)\big|<\varepsilon/2$ for $0<t<\delta$. Since $$K_N(x)=\frac{1}{N+1}\cdot\frac{1-\cos(N+1)x}{1-\cos x}$$ is an even function, we have from Exercise 15(b) that $$\frac{1}{2\pi}\int_{-\pi}^0K_N(t)\,dt=\frac{1}{2\pi}\int_0^\pi K_N(t)\,dt=\frac{1}{2}.$$Hence by the results of Exercise 15,
\begin{align*}
& \bigg|\sigma_N(f;x)-\frac{f(x+)+f(x-)}{2}\bigg| \\
& \quad\quad\le\frac{1}{2\pi}\int_{-\pi}^0\big|f(x-t)-f(x+)\big|K_N(t)\,dt + \frac{1}{2\pi}\int_0^\pi\big|f(x-t)-f(x-)\big|K_N(t)\,dt \\
& \quad\quad\le\frac{1}{2\pi}\frac{1}{N+1}\frac{2}{1-\cos\delta}\Bigg(\int_{-\pi}^{-\delta}\big|f(x-t)-f(x+)\big|\,dt+\int_\delta^\pi\big|f(x-t)-f(x-)\big|\,dt\Bigg)\;+ \\
& \quad\quad\phantom{\le}\;\;\frac{\varepsilon}{2}\Bigg(\frac{1}{2\pi}\int_{-\delta}^0K_N(t)\,dt+\frac{1}{2\pi}\int_0^\delta K_N(t)\,dt\Bigg)
\end{align*}The two integrals in the first term are finite, so we can make it as small as we would like as $N\rightarrow\infty$, and the second term is less than $\varepsilon/2$. Hence $\sigma_N(f;x) \rightarrow\big(f(x+)+f(x-)\big)/2$ as $N\rightarrow\infty$.


Exercise 17

(By analambanomenos)

(a) Using Exercise 6.17, with $G(x)=(i/n)e^{-inx}$,
\begin{align*}
nc_n &= \frac{n}{2\pi}\int_{-\pi}^\pi f(x)e^{-inx}\,dx \\
&= \frac{i}{2\pi}\big(f(\pi)e^{-in\pi}-f(-\pi)e^{in\pi}\big)-\frac{i}{2\pi}\int_{-\pi}^\pi e^{-inx}\,df \\
|nc_n| &\le \frac{1}{2\pi}\big(f(\pi)-f(-\pi)\big)+\frac{1}{2\pi}\int_{-\pi}^\pi 1\,df \\
&= \frac{1}{\pi}\big(f(\pi)-f(-\pi)\big)
\end{align*}(b) Since $|nc_n|\le M=\big(f(\pi)-f(-\pi)\big)/\pi$, we can apply Exercise 3.14(e) to get $$\lim_{N\rightarrow\infty}s_N(f;x)=\lim_{N\rightarrow\infty}\sigma_N(f;x)=\frac{f(x+)+f(x-)}{2}.$$The last equality is from Exercise 16.

(c) Letting $$\tilde{f}(x)=
\begin{cases}
f(\alpha) & -\pi\le x\le\alpha \\
f(x) & \alpha\le x\le\beta \\
f(\beta) & \beta\le x\le\pi
\end{cases}$$then $\tilde{f}$ is monotonically increasing on $[-\pi,\pi]$, so by part (b) we have $$\lim_{N\rightarrow\infty}s_N(\tilde{f};x)=\frac{\tilde{f}(x+)+\tilde{f}(x-)}{2}$$ for all $-\pi\le x\le\pi$. Hence by the localization theorem, since $f(x)=\tilde{f}(x)$ for $\alpha<x<\beta$, we have $$\lim_{N\rightarrow\infty}s_N(f;x)=\lim_{N\rightarrow\infty}s_N(\tilde{f};x)=\frac{\tilde{f}(x+)+\tilde{f}(x-)}{2}=\frac{f(x+)+f(x-)}{2}$$ for $\alpha<x<\beta$.


Exercise 18

(By analambanomenos) Note that $(d/dx)\tan x=n\tan^{n-1}x+n\tan^{n+1}x$.
\begin{align*}
f(x) &= x^3-(1-\cos^2x)\tan x \\
&= x^3+2^{-1}\sin2x-\tan x \\
f’(x) &= 3x^2 +\cos2x-1-\tan^2x \\
f”(x) &= 6x-2\sin2x-2\tan x-2\tan^3x \\
f”’(x) &= 6-4\cos2x-2-8\tan^2x-6\tan^4x \\
f^{(4)}(x) &= 8\sin2x-16\tan x-40\tan^3x-24\tan^5x \\
f^{(5)}(x) &= 16\cos2x-16-136\tan^2x-240\tan^4x-120\tan^6x \\
f^{(6)}(x) &= -32\sin2x-272\tan x-1232\tan^3x-1680\tan^5x-720\tan^7x
\end{align*}Note that $f(0)=f’(0)=f”(0)=f”’(0)=f^{(4)}(0)=f^{(5)}(0)=0$. Since $f^{(6)}(x)<0$ on $(0,\pi/2)$, $f^{(5)}$ decreases monotonically throughout that interval from $f^{(5)}(0)=0$ to $f^{(5)}(\pi/2)=-\infty$, hence the same is successively true for $f^{(4)}$, $f”’$, $f”$, $f’$, and $f$.
\begin{align*}
g(x) &= 2x^2-\sin^2x-x\tan x \\
g’(x) &= 4x-\sin2x-\tan x-x(1+\tan^2x) \\
g”(x) &= 4-2\cos2x-2-2\tan^2x-x(2\tan x+2\tan^3x) \\
g”’(x) &= 4\sin2x-6\tan x-6\tan^3x-x(2+8\tan^2x+6\tan^3x) \\
g^{(4)}(x) &= 8\cos2x-8-32\tan^2x-24\tan^4x-x(16\tan x+40\tan^3x+24\tan^5x) \\
g^{(5)}(x) &= -16\sin2x-80\tan x-200\tan^3x-120\tan^5x\;-\\
&\phantom{=}\;\; x(16+136\tan^2x+240\tan^3x+120\tan^6x)
\end{align*}Note that $g(0)=g’(0)=g”(0)=g”’(0)=g^{(4)}(0)=0$. Since $g^{(5)}(x)<0$ on $(0,\pi/2)$, $g^{(4)}$ decreases monotonically throughout that interval from $g^{(4)}(0)=0$ to $g^{(4)}(\pi/2)=-\infty$, hence the same is successively true for $g”’$, $g”$, $g’$, and $g$.


Exercise 19

(By analambanomenos) Following the hint, we first show this for trigonometric polynomials. Let $$P(x)=\sum_{m=-M}^Mc_me^{imx}.$$ Then $$\frac{1}{2\pi}\int_{-\pi}^\pi P(t)\,dt=\sum_{m=-M}^Mc_m\frac{1}{2\pi}
\int_{-\pi}^\pi e^{imt}\,dt=c_0$$ and (noting that $e^{im\alpha}\ne 1$ for $m\ne 0$ since $\alpha/\pi$ is irrational)
\begin{align*}
\frac{1}{N}\sum_{n=1}^NP(x+n\alpha) &= \frac{1}{N}\sum_{n=1}^N\sum_{m=-M}^Mc_me^{im(x+n\alpha)} \\
&= \sum_{m=-M}^Mc_me^{im\alpha}\frac{1}{N}\sum_{n=1}^Ne^{(im\alpha)n} \\
&= c_0+\sum_{\genfrac{}{}{0pt}{}{m=-M}{m\ne0}}^Mc_me^{im\alpha}\frac{1}{N}\frac{e^{im\alpha}-e^{im\alpha(N+1)}}{1-e^{im\alpha}} \\
&= c_0+\sum_{\genfrac{}{}{0pt}{}{m=-M}{m\ne0}}^Mc_me^{im(x+\alpha)}\frac{1}{N}\frac{1-e^{im\alpha N}}{1-e^{im\alpha}}.
\end{align*}Since for $m\ne0$, $$\bigg|\frac{1-e^{im\alpha N}}{1-e^{im\alpha}}\bigg|\le\frac{2}{|1-e^{im\alpha}|}<\infty$$ the limit of the sum on the right-hand side above as $N\rightarrow\infty$ is 0. Hence for every $x$, $$\lim_{N\rightarrow\infty}\frac{1}{N}\sum_{n=1}^NP(x+n\alpha)=c_0=\frac{1}{2\pi}\int_{-\pi}^\pi P(t)\,dt.$$For the general case, let $\varepsilon>0$. By Theorem 8.15 there is a trigonometric polynomial $P$ such that $\big|P(x)-f(x)\big|<\varepsilon/3$ for all real $x$. By the result above, there is a positive integer $N_0$ such that for all $N\ge N_0$ $$\Bigg|\frac{1}{N}\sum_{n=1}^NP(x+n\alpha)-\frac{1}{2\pi}\int_{-\pi}^\pi P(t)\,dt\Bigg|\le\frac{\varepsilon}{3}.$$ Hence
\begin{align*}
& \Bigg|\frac{1}{N}\sum_{n=1}^Nf(x+n\alpha)-\frac{1}{2\pi}\int_{-\pi}^\pi f(t)\,dt\Bigg| \\
& \qquad\le \frac{1}{N}\sum_{n=1}^N\big|f(x+n\alpha)-P(x+n\alpha)\big| + \Bigg|\frac{1}{N}\sum_{n=1}^NP(x+n\alpha)-\frac{1}{2\pi}\int_{-\pi}^\pi P(t)\,dt\Bigg|\;+ \\
& \qquad\phantom{\le}\;\frac{1}{2\pi}\int_{-\pi}^\pi\big|P(t)-f(t)\big|\,dt \\
& \qquad\le \frac{1}{N}\bigg(\frac{N\varepsilon}{3}\bigg)+\frac{\varepsilon}{3}+\frac{1}{2\pi}\bigg(\frac{2\pi\varepsilon}{3}\bigg) \\
& \qquad= \varepsilon
\end{align*}


Exercise 20

(By analambanomenos) The second derivative of $\log x$ is $-x^{-2}$, which is negative for $x>0$, so $\log x$ is a “concave” function (i.e., $-\log x$ is convex). The function $f(x)$ is a continuous, piecewise-linear function whose values at the endpoints of the linear segments, $f(m)$ for $m=1,2,\ldots,$ equal $\log m$, hence $f(x)\le\log x$ by the concavity of $\log x$. Also, $g(x)$ is a continuous, piecewise-linear function which is equal to $\log m$ at $m=1,2,\ldots,$ and the slope of $g(x)$ is equal to the derivative of $\log x$ at those points. That is, the linear segments of $g(x)$ are tangent to $\log x$ at those points, and so $\log x\le g(x)$, also by the concavity of the $\log x$.

\begin{align*}
\int_1^nf(x)\,dx &= \sum_{m=1}^{n-1}\int_m^{m+1}(m+1-x)\log m+(x-m)\log(m+1)\,dx \\
&= \sum_{m=1}^{n-1}\big(-\textstyle\frac{1}{2}(m+1-x)^2\log m+\frac{1}{2}(x-m)^2\log(m+1)\big)\big|_{x=m}^{x=m+1} \\
&= \textstyle\frac{1}{2}\log 1+\displaystyle\sum_{m=1}^{n-1}(\log m)+\textstyle\frac{1}{2}\log n \\
&= \log n!-\textstyle\frac{1}{2}\log n \\
\int_1^ng(x)\,dx &= \int_1^{\frac{3}{2}}(x-1+\log 2)\,dx+\sum_{m=2}^{n-1}\int_{m-\frac{1}{2}}^{m+\frac{1}{2}}\bigg(\frac{x}{m}-1+\log m\bigg)\,dx+\int_{n-\frac{1}{2}}^n
\bigg(\frac{x}{n}-1+\log n\bigg)\,dx \\
&= \textstyle\frac{1}{2}(x-1)^2\big|_{x=1}^{x=\frac{3}{2}}+\displaystyle\sum_{m=2}^{n-1}\textstyle\big(\frac{1}{2m}x^2-x+x\log m\big)\big|_{x=m-\frac{1}{2}}^{x=m+\frac{1}{2}}+
\big(\frac{1}{2n}x^2-x+x\log n\big)\big|_{x=n-\frac{1}{2}}^{x=n} \\
&= \textstyle\frac{1}{8}+\displaystyle\sum_{m=2}^{n-1}\big(1-1+\log m)+\big(\textstyle\frac{1}{2}-\frac{1}{8n}-\frac{1}{2}+\frac{1}{2}\log n\big) \\
&= \log n!-\textstyle\frac{1}{2}\log n +\frac{1}{8}\big(1-\frac{1}{n}\big) \\
&< \int_1^nf(x)\,dx+\textstyle\frac{1}{8}
\end{align*} Integrating by parts, we have $\int_1^n\log x\,dx=n\log n-1\log1-\int_1^n1\,dx=n\log n-n+1$. Hence
\begin{gather*}
-\int_1^ng(x)\,dx<-\int_1^n\log x\,dx<-\int_1^nf(x)\,dx \\
-\log n!+\textstyle\frac{1}{2}\log n-\frac{1}{8}<-n\log n+n-1<-\log n!+\frac{1}{2}\log n
\end{gather*} Adding $1+\log n!-\frac{1}{2}\log n$ to all sides, we get $$\textstyle\frac{7}{8}<\log n!-\big(n+\frac{1}{2}\big)\log n+n<1.$$And applying $\exp$ to all sides, we get
\begin{gather*}
e^{7/8}<\frac{\exp\big(\log n!\big)\exp(n)}{\exp\big(\log(n^{n+1/2})\big)}<e \\
e^{7/8}<\frac{n!e^n}{n^n\sqrt{n}}<e \\
e^{7/8}<\frac{n!}{(n/e)^n\sqrt{n}}<e
\end{gather*}

Baby Rudin 数学分析原理完整第八章习题解答

Linearity

This website is supposed to help you study Linear Algebras. Please only read these solutions after thinking about the problems carefully. Do not just copy these solutions.

Leave a Reply

Close Menu